2017
DOI: 10.2217/fca-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

PPARs: Regulators of Metabolism and As Therapeutic Targets in Cardiovascular disease. Part II: PPAR-β/δ and PPAR-γ

Abstract: The PPARs are a subfamily of three ligand-inducible transcription factors, which belong to the superfamily of nuclear hormone receptors. In mammals, the PPAR subfamily consists of three members: PPAR-α, PPAR-β/δ and PPAR-γ. PPARs control the expression of a large number of genes involved in metabolic homeostasis, lipid, glucose and energy metabolism, adipogenesis and inflammation. PPARs regulate a large number of metabolic pathways that are implicated in the pathogenesis of metabolic diseases such as metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
187
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 158 publications
1
187
0
6
Order By: Relevance
“…Research on the variance in gene expression profiles in the renal cortex of diabetic nephropathy rats treated with Rg3 showed that the PPAR signaling pathway was predominantly altered, indicating that PPAR is involved in mechanisms underlying Rg3 improving diabetic nephropathy (Wang et al, 2016). Evidence showed that PPARg may also involve in lipid metabolism (Han et al, 2017), the obesity associated with chronic hypoxia can lead to severe endothelium-dependent diastolic dysfunction, resulting in obstructive sleep apnea (OSA), whereas the PPARg agonist can significantly improve endothelial diastolic function and thus inhibit OSA (Zhang et al, 2017). Thus, whether Rg3 have effects on regulating PPARg in dyslipidemia induced AS which interfere FAK-related pathways or not have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the variance in gene expression profiles in the renal cortex of diabetic nephropathy rats treated with Rg3 showed that the PPAR signaling pathway was predominantly altered, indicating that PPAR is involved in mechanisms underlying Rg3 improving diabetic nephropathy (Wang et al, 2016). Evidence showed that PPARg may also involve in lipid metabolism (Han et al, 2017), the obesity associated with chronic hypoxia can lead to severe endothelium-dependent diastolic dysfunction, resulting in obstructive sleep apnea (OSA), whereas the PPARg agonist can significantly improve endothelial diastolic function and thus inhibit OSA (Zhang et al, 2017). Thus, whether Rg3 have effects on regulating PPARg in dyslipidemia induced AS which interfere FAK-related pathways or not have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…PPARα upregulates lipid uptake and β-oxidation of fatty acids, whereas PPARγ promotes adipocyte differentiation and adipokine production in adipose tissues to improve insulin sensitivity in diabetic patients [45][46][47]. Owing to these physiological functions in energy metabolism, PPARs are the molecular targets of metabolic disorders [48]. To assess the PPAR isoform specificity of 1 and 2, three reporter cell lines expressing luciferase genes in response to PPARα, PPARβ/δ, and PPARγ agonists were used [49].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the current study revealed that IS patients without CKD or concurrent telmisartan use for BP control may have trends of obtaining more benefits when taking pioglitazone for T2DM. It is well known that PPAR-γ may have metabolism regulating and neuroprotective effects and could have protective effects for HTN, atherosclerosis and CKD [5,6,35]. Pioglitazone, a potent PPAR-γ agonist, has demonstrated vascular protective effects in previous studies [7,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor-γ (PPAR-γ) is a known essential mediator for the maintenance of whole body insulin sensitivity [5]. Biochemical and metabolic regulators of PPAR-γ have been considered as therapeutic targets in cardiovascular diseases [6]. A previous Cochrane review demonstrated that PPAR-γ agonists may improve insulin sensitivity and probably reduce recurrent strokes and total cardiovascular death events [4].…”
Section: Introductionmentioning
confidence: 99%